Positive Outcomes of Cross-Border Tourism Development Cooperation: A Case of Kazakhstan, Kyrgyzstan and Uzbekistan - Akbar, Imanaly; Tazhekova, Akmaral; Myrzaliyeva, Zabira; Pazylkhaiyr, Bauyrzhan; Mominov, Serik (REGION, 2024)
The development of cross-border tourism between neighboring countries has become increasingly popular in recent decades. In European countries where the visa-free regime is established, this scheme is well developed and positively affects the development of the country's economy. Developing cross-border areas and establishing cross-border cooperation with neighboring countries is one of the priorities of Central Asian state policy. In the last ten years, several large-scale cross-border platforms aimed at developing tourism have been implemented among the more developed countries (Kazakhstan, Kyrgyzstan and Uzbekistan) in Central Asia, so our study was based on the border regions of the three countries mentioned above. The study aims to highlight the benefits of cooperation in cross-border tourism by examining the experiences and expectations of experts who are well-versed in the field of tourism. A qualitative research method was mainly used in semi-structured interviews focused on the positive results associated with the development of cross-border tourism among people familiar with the region's tourism. The analysis showed that according to the informants, the development of cross-border tourism has a moderate impact on the joint development of infrastructure projects by countries. The results also showed that all of the survey participants believed that cross-border tourism would provide an impetus to strengthen joint tourism marketing and the exchange of knowledge and innovation between countries. In short, it can be seen from the results of the research that the respondents generally highly appreciated the positive influence of the development of cross-border tourism on the growth of the country's economy.